Study on the effects of reliability of conflict resolution aid on the workload, performance and situation awareness of air traffic controllers - Kuo, Yi Jun (2015)
Air Traffic Control (ATC) is inevitably a vital component to ensuring flight safety. Despite the performance of Air Traffic Controllers (ATCOs) being reported to improve in the presence of Conflict Resolution Aid (CRA), the effects of reliability is still generally unknown. Holistic examination of the effects of reliability of CRA is extremely important in justifying its future application in such a demanding industry. Known effects of reliability of automation could allow better consciousness towards the CRA and therefore improving performance without leading to over-dependence on the automation and overlooking of the possibility of machine breakdowns in future applications, which is crucial to maintaining the level of flight safety at all times. This project studies the relationship between the levels of reliability of the conflict resolution aid and the workload, performance and situation awareness (SA) of the ATCOs. Situation scenarios designed with conflict resolutions were displayed to twelve participants, ranging from actual ATCOs to Aerospace Engineering students. The scenarios correspond to the three reliability conditions which were reliable, unreliable and manual conditions. The results were revealed to have a positive effect of reliability on performance, where more conflicts were resolved under reliable than under unreliable condition. The participants could however, still perform better under unreliable condition versus manual condition. It was also discovered that the level of SA was improved as there were more correct answers and shorter time was needed to respond to the SA questions when CRA was available.